Digital Design Platform of RV Reducer - Minghui Xu; Wanli Li (Jixie chuandong)
The key technology and method of RV Reducer digital design by using C# language and SolidWorks secondary development technology are introduced. Through in-depth study of the parameterization process of the RV reducer， the digitization process from the input of the overall target parameters to the specific parameters of the parts is realized. A CAD system platform for RV reducer parameter optimization design is developed， and combined with the database， the management of part parameters is realized.